Hamburgers cost $3 and hotdogs cost $2. The total cost of buying b hamburgers and d hotdogs can be expressed by C=3b+2d. How can this equation be solved for d?

A. d=C-3b/2
B. d=b-3C/2
C. d=C-3/2b
D. d=C-b

Respuesta :

C = 3b+2d is the same as 3b+2d = C

Let's isolate d. To do this, we first need to subtract 3b from both sides

3b+2d = C
3b+2d-3b = C-3b
2d = C-3b

Then divide both sides by 2

2d = C-3b
2d/2 = (C-3b)/2
d = (C-3b)/2

Take note of the parenthesis as they are very important. We want to divide ALL of C-3b over 2. We don't want to just divide -3b over 2.

The answer choices you have aren't 100% clear but I have a feeling your teacher meant to say d = (C-3b)/2 instead of d = C-3b/2 for choice A

If that assumption is correct, then the answer is choice A.